PENGARUH KONSUMSI JAMBU BIJI MERAH TERHADAP PERUBAHAN KADAR HEMOGLOBIN PADA IBU HAMIL - Septa Dwi Insani; Kristin Natalia; Naimah Nasution; Husna Sari (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Guava (Psidium guajava L) is a fruit that can be used as a functional food ingredient because it has a function for health. The functional properties of guava are caused by the presence of high enough vitamin C. The research objective was to determine the effectiveness of giving guava to increase Hb level in pregnant women. The design of this study is on experimental study with one group pre-test post test design apporoach with populastion 15 pregnant women whe have anemia and sampel get to total sampling. Variabel Independent is of red guava and variabel dependent is increase pregnant women Hb level, the research t-test. The result showed that mother’s Hb level before consume of red guava Mean Mean 1,40 gr/dl, Maximum 2 gr/dl, Minimum 1gr/dl dan Std. Deviation 0,507 gr/dl. Mother’s Hb consent after consuming of guava of read is Mean 1,20 gr/dl, Maximum 2 gr/dl, Minimum 1 gr/dl dan Std Deviation 0,414 gr/dl with p = 0,005.